Leaf area Index measurements for Pinus brutia Ten. Plantations in Northern Iraqi - Maan Shekho; Mohammed Al-Allaf; Muzahim Younis (Mesopotamia Journal of Agriculture)
The surface area of the leaves of trees that perform photosynthesis is expressed by the leaf area index (LAI) for pine trees with different densities, using direct methods by collecting field data in 2022 from (30) samples, and measurements were taken of the diameter at breast height for each sample and the total height, crown center height, crown width, and number of trees. Through field data and laboratory analysis of the relationships between the structure of tree elements, it was found that the leaf area index showed an inverse relationship with the distances between trees and that increasing the distance between trees reduces the crown coverage of trees and thus is reflected in the leaf area index of the tree. At low densities, it decreases and increases with increasing tree density. This also applies to the relationship between the dry weight of leaves and the distances between trees, as an inverse relationship showed, and this was also clear for the relationship between the dry weight of leaves and the average diameter and height of the trees in that tree. A set of equations was reached that was tested using multiple statistical standards, and it was the equation of the dry weight of pine tree leaves per unit area, the equation of the surface area of pine tree leaves per unit area, as well as the leaf area index of pine trees (LAI).